VOCATIONAL EDUCATION IN THE SYSTEM OF SATISFYING THE NEED OF ECONOMY IN MIDDLE LEVEL WORKERS - Andrey E. Shklyaev (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article assesses the present situation in providing personnel with vocational education and shows principle directions of its further development. Secondary vocational education is a level of the system of vocational education which takes a specific place in meeting educational requirements of person and society. The key objective in pursuing policy in the field of secondary vocational education implies the active participation in shaping federal, national and regional components in the program of vocational education. Today the issue of building a new system of training skilled workers is really acute. It should be developed by successive determined training of skilled and competitive workers who can use equipment of the 5th and 6th class.